A TiO2 / Cs2AgBiBr6 composite catalyst and its preparation method and application

Through the heterojunction structure of the TiO2/Cs2AgBiBr6 composite catalyst, the existing photocatalytic CO2 reduction efficiency and poor selectivity are solved, and efficient CO2 reduction to CO gas is achieved, and it meets the technical requirements of green cleaning.

CN116550345BActive Publication Date: 2024-12-17BEIJING UNIV OF TECH
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202310529010.3
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2023-05-11
Publication Date
2024-12-17
Estimated Expiration
2043-05-11

AI Technical Summary

Technical Problem

In the existing photocatalytic CO2 reduction technology, the catalyst has low efficiency, poor selectivity, and contains toxic elements. It has high synthesis cost, making it difficult to take into account both light absorption and redox reactions.

Method used

Using TiO2/Cs2AgBiBr6 composite catalyst, the nano-TiO2 catalyst is supported on the surface of Cs2AgBiBr6 crystal under water melting to form a heterojunction, which improves electron separation transfer efficiency and light absorption capacity, and promotes the efficient reduction of CO2 to CO gas under visible light.

Benefits of technology

The selectivity and yield of photocatalytic CO2 are significantly improved. The selectivity of CO is close to 100%, and the yield is much higher than that of catalysts used alone. The preparation process is simple and convenient, and it meets the goal of green cleaning.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure HDA0004223826990000011
    Figure HDA0004223826990000011
  • Figure HDA0004223826990000012
    Figure HDA0004223826990000012
  • Figure HDA0004223826990000021
    Figure HDA0004223826990000021
Patent Text Reader

Abstract

The present invention relates to a TiO2 / Cs2AgBiBr6 composite catalyst and a preparation method and application thereof, belonging to the field of photocatalysis technology. The TiO2 / Cs2AgBiBr6 composite catalyst of the present invention is composed of a nano-TiO2 catalyst and a Cs2AgBiBr6 crystal, wherein the nano-TiO2 catalyst is loaded on the surface of the Cs2AgBiBr6 crystal. The invention grinds and mixes CsBr, AgBr and BiBr3 to obtain a precursor powder; spreads the precursor powder on a weighing paper, floats the weighing paper on the surface of deionized water, and gradually infiltrates the precursor powder with deionized water; during the infiltration process, the color of the precursor powder changes from light to dark, and after the color change stops, the infiltrated powder is taken out and dried to obtain Cs2AgBiBr6 crystal powder; the Cs2AgBiBr6 crystal powder and a nano-TiO2 catalyst are added to a grinding container, and the nano-TiO2 catalyst is wet-milled for 5 to 10 minutes under the condition of relative humidity>50%, and the nano-TiO2 catalyst is loaded on the surface of the Cs2AgBiBr6 crystal to obtain a TiO2 / Cs2AgBiBr6 composite catalyst. The TiO2 nanoparticles of the invention are loaded on the Cs2AgBiBr6 crystal, effectively promote the separation and transfer of photogenerated electrons, and efficiently catalyze the reduction of CO2 gas to selectively convert it into CO gas under visible light.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to a TiO2 / Cs2AgBiBr6 composite catalyst and a preparation method and application thereof, belonging to the technical field of photocatalysis. Background Art

[0002] Photocatalytic carbon dioxide reduction uses light-driven semiconductor catalysts to catalyze the reduction of CO2 into C1 / C2 fuels such as CO, CH4, CH3OH, C2H4, HCOOH, and HCHO.

[0003] Photocatalytic CO2 reduction is a complex process, which mainly includes three key coordinated steps. The first step is that the semiconductor absorbs photons to generate electron-hole pairs, the second step is that some of the photogenerated electron-hole pairs are consumed by recombination, and the third step is the adsorption of carbon dioxide, and the remaining electron-hole pairs are transferred to undergo corresponding redox reactions. It is difficult for a single catalyst to take all of the above aspects into account, and each has its own problems to a greater or lesser extent, such as wide bandgap, rapid recombination of photogenerated carriers, and poor photoreduction potential.

[0004] To solve this problem, a composite material with a heterogeneous structure was proposed. By combining two semiconductors with a step difference in energy bands, an endogenous electric field will be formed between the two semiconductors to transfer electrons, and corresponding half-reactions will occur on the two semiconductors respectively, ensuring light absorption while improving redox ability and promoting the separation and transfer efficiency of photogenerated carriers. Composite materials are widely used in the field of photocatalysis. Finding two suitable semiconductors and combining them is a very important technical key.

[0005] However, the heterogeneous composite materials in the existing technology, such as CsPbBr3 / g-C3N4, FAPbBr3 / Bi2WO6, CsPbBr3 / ZIF-67, etc., on the one hand, contain toxic Pb elements and do not meet the goal of green cleaning; on the other hand, these materials can only be synthesized in small batches and the synthesis cost is relatively high. Summary of the invention

[0006] In view of the problems of low efficiency and poor selectivity in the prior art of photocatalytic reduction of CO2 gas for selective conversion into C1 / C2 fuel, the present invention proposes a TiO2 / Cs2AgBiBr6 composite catalyst and a preparation method and application thereof, that is, nano-TiO2 catalyst and Cs2AgBiBr6 crystals are mechanically ground under the action of water to load the nano-TiO2 catalyst on the surface of Cs2AgBiBr6 crystals to form a TiO2 / Cs2AgBiBr6 composite catalyst, and the nano-TiO2 catalyst and Cs2AgBiBr6 crystals are composited to form a heterojunction to promote the efficiency of electron separation and transfer and enhance the light absorption capacity to improve the photocatalytic performance, so that CO2 gas can be photocatalytically reduced and selectively converted into CO gas under visible light.

[0007] A TiO2 / Cs2AgBiBr6 composite catalyst is composed of a nano-TiO2 catalyst and a Cs2AgBiBr6 crystal. The mass ratio of the nano-TiO2 catalyst to the Cs2AgBiBr6 crystal is 0.5-1.5:1. The nano-TiO2 catalyst and the Cs2AgBiBr6 crystal are mechanically ground under the action of water melting so that the nano-TiO2 catalyst is loaded on the surface of the Cs2AgBiBr6 crystal.

[0008] The preparation method of the TiO2 / Cs2AgBiBr6 composite catalyst comprises the following specific steps:

[0009] (1) grinding and mixing CsBr, AgBr and BiBr3 to obtain a precursor powder;

[0010] (2) Spread the precursor powder on weighing paper, float the weighing paper on the surface of deionized water, and allow the deionized water to gradually soak the precursor powder. During the soaking process, the color of the precursor powder changes from light to dark. After the color change stops, take out the soaked powder and dry it to obtain Cs2AgBiBr6 crystal powder;

[0011] (3) Add Cs2AgBiBr6 crystal powder and nano-TiO2 catalyst into a grinding container, wet grind for 5 to 10 minutes at a relative humidity of more than 50% to load the nano-TiO2 catalyst on the surface of the Cs2AgBiBr6 crystal, and dry to obtain a TiO2 / Cs2AgBiBr6 composite catalyst.

[0012] Preferably, the molar ratio of CsBr, AgBr and BiBr3 in step (1) is 2:1:1.

[0013] Application of TiO2 / Cs2AgBiBr6 composite catalyst in visible light photocatalytic reduction of CO2 gas to CO gas.

[0014] Under visible light, the principle of photocatalytic reduction of CO2 gas into CO gas by TiO2 / Cs2AgBiBr6 composite catalyst is as follows: Figure 5 Under the action of sunlight, both Cs2AgBiBr6 and TiO2 semiconductors will produce electron transitions, with electrons jumping from the valence band (VB) to the conduction band (CB), forming a conduction band rich electron (e - ), valence band is hole-rich (h +) state. After the two materials are compounded by water-melting grinding, the two materials will form a heterogeneous structure, and the electrons on the conduction band of TiO2 will be transferred to the valence band of Cs2AgBiBr6 and promote the electron transition on the valence band of Cs2AgBiBr6; at this time, the CO2 adsorbed on the material will combine with the electrons on the conduction band of Cs2AgBiBr6, and a reduction reaction will occur to generate CO; the H2O adsorbed on the material will combine with the holes on the valence band of TiO2, and an oxidation reaction will occur to generate O2.

[0015] The beneficial effects of the present invention are:

[0016] (1) The present invention mechanically grinds nano-TiO2 catalyst and Cs2AgBiBr6 crystal under the action of water melting to load the nano-TiO2 catalyst on the surface of Cs2AgBiBr6 crystal. The process is carried out at room temperature and pressure without heating, and the preparation process is simple and convenient.

[0017] (2) The nano-TiO2 catalyst of the present invention is loaded on the surface of Cs2AgBiBr6 crystals to form a TiO2 / Cs2AgBiBr6 composite catalyst, which can promote the electron separation and transfer efficiency between the nano-TiO2 catalyst and the Cs2AgBiBr6 crystals, improve the light absorption capacity of the material, and enhance the redox ability of the material, effectively enhance the activity of the photocatalyst, and catalyze the selective reduction of CO2 gas into CO gas under visible light. BRIEF DESCRIPTION OF THE DRAWINGS

[0018] Figure 1 This is the XRD pattern of Cs2AgBiBr6 crystal powder;

[0019] Figure 2 The scanning electron microscope image and EDS image of Cs2AgBiBr6 crystal;

[0020] Figure 3 This is a scanning electron microscope image of the TiO2 / Cs2AgBiBr6 composite catalyst of Example 1;

[0021] Figure 4 This is a graph showing the photocatalytic CO2 reduction performance of the TiO2 / Cs2AgBiBr6 composite catalyst of Example 1 and pure TiO2 and pure Cs2AgBiBr6 crystals under visible light.

[0022] Figure 5 This is the photocatalytic mechanism diagram of TiO2 / Cs2AgBiBr6 composite catalyst;

[0023] Figure 6 These are the chromatographic detection data of gas produced by TiO2 / Cs2AgBiBr6 composite catalyst and pure TiO2 and pure Cs2AgBiBr6 crystals under visible light for 4 hours. DETAILED DESCRIPTION

[0024] The present invention is further described in detail below in conjunction with specific implementation modes, but the protection scope of the present invention is not limited to the described contents.

[0025] Example 1: A TiO2 / Cs2AgBiBr6 composite catalyst is composed of a nano-TiO2 catalyst and a Cs2AgBiBr6 crystal. The mass ratio of the nano-TiO2 catalyst to the Cs2AgBiBr6 crystal is 0.5:1. The nano-TiO2 catalyst and the Cs2AgBiBr6 crystal are mechanically ground under the action of water so that the nano-TiO2 catalyst is loaded on the surface of the Cs2AgBiBr6 crystal.

[0026] The preparation method of the TiO2 / Cs2AgBiBr6 composite catalyst comprises the following specific steps:

[0027] (1) grinding and mixing CsBr, AgBr and BiBr3 for 10 minutes to obtain a precursor powder; wherein the molar ratio of CsBr, AgBr and BiBr3 is 2:1:1;

[0028] (2) Spread the precursor powder on weighing paper, float the weighing paper on the surface of deionized water, and allow the deionized water to gradually soak the precursor powder. During the soaking process, the color of the precursor powder changes from light to dark. After the color change stops, take out the soaked powder and dry it to obtain Cs2AgBiBr6 crystal powder;

[0029] The XRD spectrum of the Cs2AgBiBr6 crystal powder in this example is shown in Figure 1 ,from Figure 1 It can be seen that by comparing the diffraction peaks of Cs2AgBiBr6 with the standard peaks on the standard Cs2AgBiBr6PDF card one by one, it is found that the peak positions and peak intensities are completely composite, proving that the catalyst synthesized in Example 1 is pure Cs2AgBiBr6;

[0030] The SEM and EDS images of the Cs2AgBiBr6 crystal powder in this example are shown in Figure 2 ,from Figure 2 It can be seen that the crystal size of the pure Cs2AgBiBr6 catalyst synthesized in Example 1 ranges from 100 to 600 nm; Figure 2 .b is an EDS graph, which shows that the molar ratio of Cs, Ag, Bi, and Br elements in the pure Cs2AgBiBr6 catalyst synthesized in Example 1 is approximately 2:1:1:6, and the element ratio is consistent with that of the pure Cs2AgBiBr6 catalyst;

[0031] (3) adding Cs2AgBiBr6 crystal powder and nano-TiO2 catalyst into a grinding container, wet grinding for 8 min at a relative humidity of >50% to load the nano-TiO2 catalyst on the surface of the Cs2AgBiBr6 crystal, and then drying at 80°C to obtain a TiO2 / Cs2AgBiBr6 composite catalyst;

[0032] The scanning electron microscope image of the TiO2 / Cs2AgBiBr6 composite catalyst in this example is shown in Figure 3 ,Depend on Figure 3 It can be seen that the brighter ones are TiO2 nanoparticles, and the darker ones are Cs2AgBiBr6 crystals. After the two are combined, the smaller TiO2 particles are attached to Cs2AgBiBr6 to form a heterojunction.

[0033] The photocatalytic CO2 reduction performance of TiO2 / Cs2AgBiBr6 composite catalyst, pure TiO2 (P25, Aladdin, 99.9%) and pure Cs2AgBiBr6 crystals was tested under visible light: 100 mg of sample was taken and dispersed on a glass dish, 10 ml of water was added to the reactor, and the glass dish carrying the sample was placed in the reactor (the sample was not in direct contact with water), and then the reactor was installed in the Meiruichen photocatalytic integrated equipment (the equipment has its own light source and cooling circulation device), and the reaction was continued for 4 hours. 1 ml of gas was taken from the equipment every hour and injected into the gas chromatograph to detect the product CO. The photocatalytic CO2 reduction performance is shown in FIG. Figure 4 ,from Figure 4 It can be seen that the CO production of TiO2 / Cs2AgBiBr6 composite catalyst in 4 hours is Figure 4 , is 22.6umol / g, and its yield is nearly 12.5 times that of pure Cs2AgBiBr6 catalyst and 2.8 times that of pure TiO2;

[0034] The chromatographic detection data of the gas produced by the photocatalytic TiO2 / Cs2AgBiBr6 composite catalyst and pure TiO2 and pure Cs2AgBiBr6 crystals under visible light for 4 hours are shown in Figure 6 As can be seen from the figure, the performance of the TiO2 / Cs2AgBiBr6 composite catalyst is greatly improved compared with pure TiO2 and pure Cs2AgBiBr6 crystals; the selectivity of the product is also greatly improved, and the selectivity of CO is almost 100%.

[0035] Example 2: A TiO2 / Cs2AgBiBr6 composite catalyst is composed of a nano-TiO2 catalyst and Cs2AgBiBr6 crystals, wherein the mass ratio of the nano-TiO2 catalyst to the Cs2AgBiBr6 crystals is 1:1. The nano-TiO2 catalyst and the Cs2AgBiBr6 crystals are mechanically ground under the action of water so that the nano-TiO2 catalyst is loaded on the surface of the Cs2AgBiBr6 crystals.

[0036] The preparation method of the TiO2 / Cs2AgBiBr6 composite catalyst comprises the following specific steps:

[0037] (1) grinding and mixing CsBr, AgBr and BiBr3 for 10 minutes to obtain a precursor powder; wherein the molar ratio of CsBr, AgBr and BiBr3 is 2:1:1;

[0038] (2) Spread the precursor powder on weighing paper, float the weighing paper on the surface of deionized water, and allow the deionized water to gradually soak the precursor powder. During the soaking process, the color of the precursor powder changes from light to dark. After the color change stops, take out the soaked powder and dry it to obtain Cs2AgBiBr6 crystal powder;

[0039] (3) Cs2AgBiBr6 crystal powder and nano-TiO2 catalyst were added to a grinding container, and the nano-TiO2 catalyst was loaded on the surface of the Cs2AgBiBr6 crystal by wet grinding for 6 minutes under the condition of relative humidity>50%, and then dried at a temperature of 70°C to obtain a TiO2 / Cs2AgBiBr6 composite catalyst; the photocatalytic CO2 reduction performance of the TiO2 / Cs2AgBiBr6 composite catalyst was tested under visible light, and the CO production of the TiO2 / Cs2AgBiBr6 composite catalyst in 4 hours was as follows: Figure 4 , which is 31.0umol / g. Its yield is nearly 17 times that of pure Cs2AgBiBr6 catalyst and nearly 3.9 times that of pure TiO2.

[0040] Example 3: A TiO2 / Cs2AgBiBr6 composite catalyst is composed of a nano-TiO2 catalyst and Cs2AgBiBr6 crystals, wherein the mass ratio of the nano-TiO2 catalyst to the Cs2AgBiBr6 crystals is 1.5:1. The nano-TiO2 catalyst and the Cs2AgBiBr6 crystals are mechanically ground under the action of water so that the nano-TiO2 catalyst is loaded on the surface of the Cs2AgBiBr6 crystals.

[0041] The preparation method of the TiO2 / Cs2AgBiBr6 composite catalyst comprises the following specific steps:

[0042] (1) grinding and mixing CsBr, AgBr and BiBr3 for 10 minutes to obtain a precursor powder; wherein the molar ratio of CsBr, AgBr and BiBr3 is 2:1:1;

[0043] (2) Spread the precursor powder on weighing paper, float the weighing paper on the surface of deionized water, and allow the deionized water to gradually soak the precursor powder. During the soaking process, the color of the precursor powder changes from light to dark. After the color change stops, take out the soaked powder and dry it to obtain Cs2AgBiBr6 crystal powder;

[0044] (3) adding Cs2AgBiBr6 crystal powder and nano-TiO2 catalyst into a grinding container, wet grinding for 10 min under the condition of relative humidity>50% to load the nano-TiO2 catalyst on the surface of Cs2AgBiBr6 crystal, and then drying at 70°C to obtain TiO2 / Cs2AgBiBr6 composite catalyst;

[0045] The photocatalytic CO2 reduction performance of the TiO2 / Cs2AgBiBr6 composite catalyst was tested under visible light. The CO production of the TiO2 / Cs2AgBiBr6 composite catalyst in 4 hours was Figure 4 , which is 27.9umol / g. Its yield is nearly 15.5 times that of pure Cs2AgBiBr6 catalyst and 3.5 times that of pure TiO2.

[0046] The specific implementation modes of the present invention are described in detail above, but the present invention is not limited to the above implementation modes, and various changes can be made within the knowledge scope of ordinary technicians in this field without departing from the purpose of the present invention.

Claims

1. A TiO2 / Cs2AgBiBr6 composite catalyst, characterized in that: The method is composed of nano-TiO2 catalyst and Cs2AgBiBr6 crystals, wherein the mass ratio of the nano-TiO2 catalyst and the Cs2AgBiBr6 crystals is 0.5-1.5:1, and the nano-TiO2 catalyst and the Cs2AgBiBr6 crystals are mechanically ground under the action of water melting so that the nano-TiO2 catalyst is loaded on the surface of the Cs2AgBiBr6 crystals; The preparation method of the TiO2 / Cs2AgBiBr6 composite catalyst comprises the following specific steps: (1) Grinding and mixing CsBr, AgBr and BiBr3 to obtain a precursor powder; (2) Spread the precursor powder on weighing paper, float the weighing paper on the surface of deionized water, and allow the deionized water to gradually soak the precursor powder. During the soaking process, the color of the precursor powder changes from light to dark. After the color change stops, take out the soaked powder and dry it to obtain Cs2AgBiBr6 crystal powder; (3) Add Cs2AgBiBr6 crystal powder and nano-TiO2 catalyst into a grinding container, wet grind for 5-10 min at a relative humidity of >50% to load the nano-TiO2 catalyst on the surface of the Cs2AgBiBr6 crystal, and dry to obtain a TiO2 / Cs2AgBiBr6 composite catalyst.

2. The TiO2 / Cs2AgBiBr6 composite catalyst according to claim 1, characterized in that: Step (1) The molar ratio of CsBr, AgBr and BiBr3 is 2:1:

1.

3. Use of the TiO2 / Cs2AgBiBr6 composite catalyst according to claim 1 or 2 in visible light photocatalytic reduction of CO2 gas into CO gas.

Citation Information

Patent Citations

  • Method for degrading monatomic transition element photocatalyst of organic medicine

    CN114160153A

  • Preparation method of titanium dioxide / lead-free halogen perovskite composite photocatalytic material

    CN114308084A

  • Method for preparing composite photocatalyst

    CN114405530A

  • Z-type heterojunction Cs2AgBiBr6 / TiO2 composite material and preparation method thereof

    CN115970715A